Dietary inflammatory index and type 2 diabetes in US women: a cross-sectional analysis of the National Health and Nutrition Examination Survey, 2007–2018 - Mo, Tingyan; Wei, Man; Fu, Jinyan (Frontiers in Nutrition, 2024)
Objective: Type 2 diabetes(T2D) is a major public health concern in the United States and worldwide.The dietary inflammatory index (DII) is a useful tool for assessing dietary inflammation.Although much research links the DII to diabetes, little is known about the relationship in adult women with a reproductive history in the United States. We aimed to investigate how the relationship between the DII and T2D varies among different subgroups of American women. Methods: Secondary data from the National Health and Nutrition Examination Survey from 2007 to 2018 were analyzed. Cross sectional analysis of 8,394 American women aged 20 years or older who had at least one live birth.The main outcome was the diagnosis of T2D. Multivariate survey-weighted regression was used to determine the odds ratio (OR) and 95% confidence interval (95%CI) for the association between DII and T2D. A weighted restricted cubic spline(RCS) model was constructed to establish OR curves at three knots to examine the dose-response association between DII and T2D.Additionally, a weighted subgroup analysis was performed in a fully adjusted model to verify that the association was robust.Results:The study main found a significant association between the DII and T2D (OR = 1.19,95%CI:1.12,1.26,p<0.001). Participants in the highest third of DII scores had a 56% increased risk of T2D (OR = 1.56, 95%CI:1.16,2.10; p for trend = 0.003) compared with those in the lowest third of DII scores, after adjusting for all covariates.The multivariable RCS demonstrated a linear association between DII and T2D (p= 0.892). The subsidiary found that subgroup analyses revealed a significant variation in the association between DII and T2D according to obesity, oral health, and poverty-income ratio (PIR) status. Among non-obese women, the OR was 1.22 (95%CI:1.08,1.37); among women with good oral health, the OR was 1.17 (95%CI:1.07,1.28); among women with low PIR, the OR was 1.17 (95%CI:1.05,1.30); and among women with high PIR, the OR was 1.26 (95% CI:1.07,1.48). Conclusion:Our findings suggest that there is a significant association between DII and T2D and that oral health, obesity, and PIR status may influence the relationship between DII and T2D risk. Further studies are warranted to validate our results.